A convergent formal [4 + 2] cycloaddition of 1, 6-diynes and benzyl azides: construction of spiro-polyheterocycles. Issue 17 (17th April 2018) - Bao, Ming; Lu, Wei; Su, Han; Qiu, Lihua; Xu, Xinfang
Abstract : A convergent one-pot formal [4 + 2] cycloaddition reaction for the construction of structurally appealing spiro-tetrahydroquinolines has been developed. Abstract : A convergent formal [4 + 2] cycloaddition reaction for the construction of structurally appealing spiro-tetrahydroquinolines has been developed, in which, a one-pot reaction is established for the in situ generation of two reagents, a cyclic alkyne and an N -aryliminium ion, from the corresponding precursors in the presence of an Au-catalyst and Brønsted acid, respectively.